The effect of tax understanding and individual taxpayer education level on msme compliance in npwp ownership: A survey of MSMEs in Mapanget District, Manado City - Nazillah Diva Adnayah Mardatillah; Harijanto Sabijono; Wulan D. Kindangen (The Contrarian : Finance, Accounting, and Business Research, 2026)
MSME compliance in Taxpayer Identification Number (NPWP) ownership remains low in Mapanget District, Manado City, and is thought to depend on taxpayers' tax understanding and educational background. This study examines the effect of tax understanding (X1) and individual taxpayer education level (X2) on MSME compliance in NPWP ownership (Y) using a quantitative survey of 95 MSME actors selected through purposive sampling. Data were analyzed with multiple linear regression in SPSS after instrument validity/reliability and classical assumption tests. Tax understanding had a positive and significant effect on compliance (B=0.959; t=28.960; Sig.<0.001), while education level had no significant effect (B=0.268; t=1.089; Sig.=0.279). The model was significant overall (F(2,92)=790.50; Sig.<0.001) and explained 94.4% of the variance (Adjusted R2=0.944). Given this unusually large effect size, a Harman's single-factor test indicated that common-method bias is unlikely to fully explain the result (single-factor variance=41.7%). These findings suggest that tax understanding, not formal education, is the dominant driver of formal MSME tax compliance, implying that tax authorities and MSME support agencies should prioritize understanding-based over credential-based compliance interventions.